2012
DOI: 10.4103/0976-237x.95095
|View full text |Cite
|
Sign up to set email alerts
|

Compound odontoma

Abstract: Odontomas have been extensively reported in the dental literature, and the term refers to tumors of odontogenic origin. Though the exact etiology is still unknown, the postulated causes include: local trauma, infection, inheritance and genetic mutation. The majority of the lesions are asymptomatic; however, may be accompanied with pain and swelling as secondary complaints in some cases. Here, we report a case of a compound odontome in a 14 year old patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 4 publications
0
23
0
5
Order By: Relevance
“…(7), quienes confirmaron además, que las lesiones en general son hamartomas (malformación del tejido local y sin posibilidades de crecimiento autónomo) y no son neoplásicos, y que el tipo compuesto está formado por un número variable de estructuras parecidas a dientes y la histología muestra tejidos dentales en un patrón ordenado, factor que los diferencia del tipo complejo. Por lo general se diagnostica durante exá-menes radiográficos de rutina o debido a la erupción tardía de dientes permanentes por la persistencia de los dientes deciduos; como se presentó en éste caso clínico, también, la mayoría de los odontomas se asocian a alteraciones patológicas en los dientes vecinos como: desvitalización, aplasia, malformación, reabsorción e impactación (2,8). Los odontomas deben ser removidos quirúrgicamente, seguidos del estudio histológico que proporciona el diagnóstico de certeza.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…(7), quienes confirmaron además, que las lesiones en general son hamartomas (malformación del tejido local y sin posibilidades de crecimiento autónomo) y no son neoplásicos, y que el tipo compuesto está formado por un número variable de estructuras parecidas a dientes y la histología muestra tejidos dentales en un patrón ordenado, factor que los diferencia del tipo complejo. Por lo general se diagnostica durante exá-menes radiográficos de rutina o debido a la erupción tardía de dientes permanentes por la persistencia de los dientes deciduos; como se presentó en éste caso clínico, también, la mayoría de los odontomas se asocian a alteraciones patológicas en los dientes vecinos como: desvitalización, aplasia, malformación, reabsorción e impactación (2,8). Los odontomas deben ser removidos quirúrgicamente, seguidos del estudio histológico que proporciona el diagnóstico de certeza.…”
Section: Discussionunclassified
“…La etiología es desconocida pero se relaciona con factores traumá-ticos, infecciosos, factores hereditarios, alteraciones durante la embriogénesis, hiperactividad odontoblás-tica y mutaciones genéticas (1,2). La Organización Mundial de la Salud clasifica odontomas desde el punto de vista histopatológico como: odontoma complejo y compuesto, el primero, corresponde a una alteración de la odontogénesis.…”
Section: Introductionunclassified
“…This information corroborates the case report, in which it was observed a radiolucent unilocular image and displacement of tooth #43. Odontomas are odontogenic tumors that most affect the population [28], and 67% of tumors in maxillary bones are classified as complex odontoma and compound odontoma [20]. According to Oliveira et al [16], the frequency with compound odontoma occurs in 9% to 37% of cases; and complex odontoma 5% to 30% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of Complex Odontomas is unknown. Several theories have been proposed, including local trauma, infection, family history, and genetic mutation (Gardeners's and Harmann's syndrome) [6] . It has also been suggested that odontomas are inherited from a mutant gene or interference, possibly postnatal with the genetic control of tooth development [7] .…”
Section: Discussionmentioning
confidence: 99%